2017
DOI: 10.18088/ejbmr.2.4.2016.pp7-11
|View full text |Cite
|
Sign up to set email alerts
|

The theory of dielectrophoresis and its applications on medical and materials research

Abstract: Dielectrophoresis (DEP) utilizes the polarizability of dielectric colloidal scale objects to drive their motions under a non-uniform AC electric field. It enables a non-invasive, reversible approach to manipulating colloidal particles. DEP requires particles to have the size within the range between hundreds of nanometers to tens of micrometers and a dielectric constant opposite to the liquid medium, which then could allow relatively sophisticated manipulation of a wide variety of colloidal scale objects, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…The purpose of peptide conjugated nanoparticles is hence more efficient in treatment delivery and effects. Tumor targeting ability as tested with a xenograft model supports this assessment 36,37 .…”
Section: Peptide-conjugated Lipid Nanoparticlesmentioning
confidence: 66%
“…The purpose of peptide conjugated nanoparticles is hence more efficient in treatment delivery and effects. Tumor targeting ability as tested with a xenograft model supports this assessment 36,37 .…”
Section: Peptide-conjugated Lipid Nanoparticlesmentioning
confidence: 66%
“…It is observed that the co-delivery therapy for cancer is a promising mechanism as the undesirable toxicity is eliminated. Administration of the two drugs -fluorouracil and paclitaxel can improve efficiency in the treatment of MDR cancer [34][35][36][37][38] .…”
Section: The Effectiveness Of Co-delivery Therapymentioning
confidence: 99%
“…Both Dox and 5-Fu will have to be loaded into micelles, and they improve hydrogen bond and electrostatic interactions. The co-delivery of 5-Fu and Dox is found to reduce the duration of tumor in the body and also minimize cancercausing agents 37,38 . The enhanced process of drug release is found to target the affected cells and induce the toxics that can help achieve a reduced cancer effect.…”
Section: Peptide-based Drug Deliverymentioning
confidence: 99%